Ammonia volatilization, forage accumulation, and nutritive value of marandu palisade grass pastures in different n sources and doses - da Cruz Corrêa, Darlena Caroline [UNESP]; Cardoso, Abmael da Silva [UNESP]; Ferreira, Mariane Rodrigues [UNESP]; Siniscalchi, Débora [UNESP]; Gonçalves, Pedro Henrique de Almeida [UNESP]; Lumasini, Rodolfo Nussio [UNESP]; Reis, Ricardo Andrade [UNESP]; Ruggieri, Ana Cláudia [UNESP] (MDPI, 2021)
The reduction in ammonia (NH3) losses from volatilization has significant implications in forage production. The objective of this study was to evaluate the impact of N fertilizers (urea, ammonium nitrate, and ammonium sulfate) and four doses (0, 90, 180 and 270 kg N ha−1) on N losses by NH3 volatilization, accumulation, and forage chemical composition of Urochloa brizantha cv Marandu. Two field experiments were conducted to measure NH3 losses using semi-open chambers. The forage accumulation and chemical composition were evaluated in the third experiment; the response variables included forage accumulation, crude protein (CP), and neutral detergent fiber (NDF). Compared to urea, ammonium nitrate and ammonium sulfate reduced NH3 losses by 84% and 87% and increased total forage accumulation by 14% and 23%, respectively. Forage accumulation rate and CP increased linearly with the N levels, while NDF contents decreased linearly with the N levels. In both experiments, NH3 losses and forage characteristics were different according to the rainfall pattern and temperature variations. Our results indicate that the use of nitric and ammoniacal fertilizers and the application of fertilizer in the rainy season constitute an efficient fertilizer management strategy to increase forage yield and decrease losses from volatilization of NH3.
Keywords: Ammonia volatilization; Ammonium sulfate; Crude protein; N pollution; Pastures